Atomic-scale homogeneous plastic flow beyond near-theoretical yield stress in a metallic glass - Jiaxin Yu (Nature Portfolio, 2021)
Metallic glasses display a high yield strength and typically deform via heterogeneous shear bands beyond the yield point. Here, deformation of as little as 1000 atoms in a Pt-based metallic glass at room temperature leads to near-theoretical yield strength, beyond which homogeneous deformation occurs.